The $γ $-support as a micro-support - Asano, Tomohiro; Guillermou, Stéphane; Humilière, Vincent; Ike, Yuichi; Viterbo, Claude (Comptes Rendus. Mathématique)
We prove that for any element $L$ in the completion of the space of smooth compact exact Lagrangian submanifolds of a cotangent bundle equipped with the spectral distance, the $γ $-support of $L$ coincides with the reduced micro-support of its sheaf quantization. As an application, we give a characterization of the Vichery subdifferential in terms of $γ $-support.